Identification of Competence-Repressing Factors During Log-Phase Growth of Haemophilus influenzae - Miller, Donald H. (1972)
Metabolic factors that suppress development of competence in Haemophilus influenzae during growth in the synthetic medium MI(c) have been identified. These include inosine, nicotinamide adenine dinucleotide, glycerol, and uracil. It is also possible to initiate competence in the presence of these substances if the oxygen tension in the culture is temporarily reduced.